2020
DOI: 10.21815/jde.019.188
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of Effective Clinical Teachers in Dental Hygiene Education

Abstract: Many health professions have identified characteristics of an effective clinical instructor and used this information to create tools to measure clinical teaching effectiveness (CTE) in their disciplines. However, minimal research has been conducted to explore the attributes of an effective clinical instructor in dental hygiene education. The aim of this study was to identify the attributes of dental hygiene clinical instructors associated with effective teaching. This study used a Delphi research design to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The nature of helpful feedback has been investigated by numerous researchers. One group of authors concluded that feedback should be specific, timely, consistent, constructive, nonjudgmental, and nonpersonal 2,8,12,13,14,17,18 . Fotheringham 13 states that significant learning can occur when feedback is informative, supportive, constructive, specific, and of a positive nature.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of helpful feedback has been investigated by numerous researchers. One group of authors concluded that feedback should be specific, timely, consistent, constructive, nonjudgmental, and nonpersonal 2,8,12,13,14,17,18 . Fotheringham 13 states that significant learning can occur when feedback is informative, supportive, constructive, specific, and of a positive nature.…”
Section: Introductionmentioning
confidence: 99%